2012
DOI: 10.1177/120347541201600507
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic Protoporphyria: Spectrum of Three Cases

Abstract: Erythropoietic protoporphyria should be suspected in any cases of childhood photosensitivity. Systemic complications are unusual. Mutation analysis confirms the diagnosis. Photoprotection is the cornerstone of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The most common symptoms reported were burning, pain, swelling, tingling, itching, sensitivity to touch, warmth/heat sensation, blisters, redness/discoloration, and sensitivity to hot/cold, which is consistent with previous studies. 1 , 3 Though burning and pain were reported as distinct symptoms by some participants, consistent with previous studies and case reports, 5 , 28 , 29 others reported “burning pain”. It is likely patients interpret these concepts on a continuum when describing their symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…The most common symptoms reported were burning, pain, swelling, tingling, itching, sensitivity to touch, warmth/heat sensation, blisters, redness/discoloration, and sensitivity to hot/cold, which is consistent with previous studies. 1 , 3 Though burning and pain were reported as distinct symptoms by some participants, consistent with previous studies and case reports, 5 , 28 , 29 others reported “burning pain”. It is likely patients interpret these concepts on a continuum when describing their symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the severity of these symptoms, permanent cutaneous changes were almost indiscernible, which, although unusual, has been described in cases previously. 12 , 13 It follows that since patients with EPP have a risk of liver failure, hepatotoxic medications should also be avoided. Systemic cimetidine has had promising results in a few cases.…”
Section: Discussionmentioning
confidence: 99%